Sistem Informasi Penjualan Buku Agama Islam Berbasis Website Pada Toko Buku Al-Barkah - Eko Saputra; Safrul Hamdani (Ikatan Ahli Informatika Indonesia, 2020)
Very rapid technological developments directly or indirectly affect the trading system. At present, only by accessing e-Commerce through the internet, we can choose the desired items, know the details of the goods and can make transactions with anyone without being limited by time and distance. The purpose of this study is to facilitate the inputting and processing of book data, online book sales transactions, and simplify the book sales service to consumers. With the implementation of a website-based Islamic religious book sales information system on the Al-Barkah Bookstore using the PHP and MYSQL programming language, consumers find it easier to find books of Islamic religion that are trusted with their knowledge without having to come directly to the bookstore, in payment, consumers can make transactions through transfer via mobile banking or ATM, while for reports on sales and checking of goods for bookstore owners becomes easier. The research methodology used is Research & Development.